Pengembangan Indeks Ketahanan Pangan Rumah Tangga dan Kaitannya dengan Tingkat Kecukupan Zat Gizi dan Status Gizi Anak Balita - Sutyawan Sutyawan; Ali Khomsan; Dadang Sukandar (Amerta Nutrition, 2019)
Background: Household food insecurity is a underlaying causes on undernutrition problems in children under five years. Household food security especially from food acces dimention is reflected from many indicators that are complex and easier to understand in a composite index.